Gendered barriers and opportunities in Kenya's informal dairy sector: enhancing gender-equity in urban markets. (27th June 2022) - Galiè, Alessandra; Njiru, Nelly; Heckert, Jessica; Myers, Emily; Alonso, Silvia
Abstract: Informal milk trading in peri-urban Nairobi plays a key role in supporting both livelihoods and nutrition, particularly among poor households. Gender dynamics affect who is involved in and benefits from milk trading. To better understand gendered constraints and opportunities in informal, peri-urban dairy marketing, a qualitative study was conducted in 2017 with 45 men and 50 women milk traders in Dagoretti, a peri-urban area of Nairobi, Kenya. The findings show that milk trading is more lucrative for older men than for women and younger men among the respondents. This article illustrates the differences between these women's and men's experiences as milk traders and explores the reasons behind these differences. It discusses the implications of the findings for agricultural research and development interventions that aim to enhance the sustainability and equity of the dairy sector.